Comparing quality of life in lower extremity tumor patients undergoing limb salvage surgery and amputation: a meta-analysis - Banskota, Nishant; Lei, Senlin; Yuan, Dechao; Fang, Xiang; Banskota, Sonali; Zhang, Wenli; Duan, Hong (Frontiers in Oncology, 2024)
Purpose: Limb salvage surgery and amputation are two commonly performed procedures for lower extremity tumors. When comparing these procedures in tumor patients, it is important to consider their impact on quality of life (QOL) and functional mobility. These patients often experience physical, emotional, and psychological challenges, making these factors crucial in determining the most suitable treatment approach.The outcomes of lower extremity tumors patients for QOL were collected from PubMed, MEDLINE, EMBASE, Cochrane, and Google Scholar until 28 February 2023. The physical function, mental health, role function, social function, emotional function, TESS, and MSTS outcomes were analyzed to determine the differences between the two procedures.Results: Five articles were included according to the selection criteria with a total of 245 patients.The standard mean difference (SMD) values of each parameter were slightly higher in limb salvage surgery patients but not higher enough to produce statistically significant results, the SMD values for physical function and mental health were 0.72 and 0.04 respectively. This study did not report any heterogeneity or publication bias.4 Conclusions: QOL is a large and enhanced term, which carries its importance and is challenging to compare between any procedures. The minimal rise in SMD of different QOL parameters highlighted only a slight advantage of limb salvage surgery over amputation. Therefore, further research is required to explore the impact of this crucial topic.